Perubahan Mata Pencaharian Masyarakat dari Peternak Sapi Perah menjadi Petani Labu Siam di Kampung Cigiri, Desa Cibodas, Kecamatan Pasir Jambu, Kabupaten Bandung - Johan, Berliana; Dalfa; Marliana, Dina (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Indonesia relies on the agricultural sector with the majority of the population as farmers, playing an important role in the economy with significant contributions from the agriculture, livestock, forestry and fisheries sectors. Bandung Regency has geographical potential and local wisdom. Agricultural development aims to increase production, exports, farmers' income, employment, including horticulture. In Cibodas Village, the majority of the population are farmers and dairy farmers, facing constraints in milk production and forage feed. Bandung Regency, especially Pasirjambu, a producer of vegetables, the research focuses on changing farmers into chayote farmers. Service with the Sisdamas method, identifying potential and problems. Qualitative methods, interviews, observations, FGDs, and survey data. Livelihood change factors: Economic Factors, Resource Access, and Environmental Change.